#TITLE_ALTERNATIVE# - ADE RIYATNA (nim : 12405023), RIFKI
The presence of stretch effect due to normal move out (NMO) correction degrades stack resolution and cause errors in AVO analysis. This final project tries to apply a correction method of stretch effect that derived analytically. Implementation of the stretch effect correction is done by using Wiener deconvolution methods that applied to entire angle gather. The required input is an extracted wavelet from any known reflection angle. The result of the correction operator (filter) is assumed stationary for each trace in the domain angle gather. Application of this method to synthetic and real data show that traces resolution on far offset can be improved. This method is very useful to angle gather with a fairly large angle (angle > 40Ã‚Â°).